Polarization scattering property of cascaded polarization controllers - Muga, Nelson J. (2012)
The relation between the allowed range of variation of polarization controller wave-plates angles and the respective polarization scattering properties is investigated It is demonstrated that a nearly uniform polarization scattering over the Poincare sphere is obtained using a concatenation of three polarization controllers with angles randomly changed between -pi/4 and pi/4. It is also shown that an improvement of the scattering properties is obtained if the configuration angles are allowed to change between -pi/2 and pi/2.